Utilizing excess stocks of seasonal fruit into marketable smoothie products as an effort to improve the economy of the North Bekasi Bay Pucung Umkm Community - Julian, Mezi; Saputro, Lilik Edi; Wardani, Dyah Mustika; Fahreza, Gilang (PT FORMOSA CENDEKIA GLOBAL, 2024)
Smoothies with seasonal fruits have become a rapidly growing focus of research in the context of a healthy lifestyle and culinary innovation. This article provides an in-depth overview of the concept and popularity of smoothies, particularly those utilizing seasonal fruits, as a healthy and refreshing beverage alternative. Additionally, this article highlights the trend of using spices as additives to smoothies, introducing a new dimension in terms of flavor and health benefits. Sustainability and flexibility in choosing seasonal fruits offer a variety of flavors and rich nutrients. This research outlines the potential development of smoothies with seasonal fruits as a beverage choice aligned with the demands of a healthy lifestyle and the evolving preferences of consumers. The significance of selecting seasonal fruits as the main ingredient in smoothies creates a beverage that is not only delicious but also meets the nutritional needs of the body. Various seasonal fruits like mangoes, strawberries, and oranges, rich in vitamin C and fiber, contribute positively to health. The uniqueness of smoothies with seasonal fruits lies in their ability to respond to seasonal changes, providing a natural variety of flavors.